Comunidade quilombola São Manoel: um estudo acerca do currículo escolar - VALADARES, Nelnice do Carmo (2019)
The present work was developed in the Quilombola Community of São Manoel, and aims to analyze if the cultural knowledge and practices of the Community, conceived as an educational experience, are applied or not in the school through its curriculum. The research is ethnographic and developed following the methodology of qualitative research, being carried out between the months of December 2017 and May 2018. It began with bibliographical research, in sequence were conducted semi-structured interviews with local residents, teachers and parents participation in school and in the community. The research was divided in three moments: In the first one, it was directed to the data collection about the historical process of the community. In the second, the research turned to the school space and, in the third, was directed the analysis about the curriculum developed by the School Institution. The theoretical contribution was based on Brandão (2007), Silva (2004), Libâneo (1994), Petersen (1991), among others that discuss this problem. As results we obtain that the school presents in its curriculum some elements that take us to consider to the applicability of the educational experience of its clientele, although timidly. Considering this statement, I conclude by saying that the cultural identity of a group is constituted by means of its way of thinking, speaking, living and relating to one another, through forms and customs perpetuated from generation to generation, group, a particular characteristic, which defines them as belonging to a particular society. In Silva's (2000) perspective, identity, like difference, is a social and cultural product, that is, it is produced in the social context where interpersonal relationships occur.